2017
DOI: 10.1007/s40268-017-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia Alters the Pharmacokinetics of Posaconazole and Vincristine Upon Co-Administration in Rats

Abstract: ObjectivesCo-administration of posaconazole (PSZ) and vincristine (VCR) in the treatment of patients with acute lymphoblastic leukemia increases the neurotoxicity of VCR. Our aim is to study the effect of increased lipoprotein levels on the pharmacokinetics of PSZ and VCR upon co-administration in rats.MethodsRats were assigned to three groups, normolipidemic (NL), intermediate hyperlipidemic (IHL), and extreme hyperlipidemic (HL) groups. All rats were administered PSZ orally followed by VCR intravenously 4 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…The t 1/2 of Gb in NL rats was calculated as 19.51 h while the t 1/2 in HL rats was noted as 7.59 h, although the difference was not significant. The results of present study are in agreement with the previous findings that reported lesser t 1/2 of investigated drug in HL rats ( Katnapally et al, 2009 , Khalil et al, 2017 , Khalil et al, 2016 ). The CL of Gb in NL rats was recorded as 2.53 ml/h while the CL in HL rats was noted as 1.39 ml/h.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The t 1/2 of Gb in NL rats was calculated as 19.51 h while the t 1/2 in HL rats was noted as 7.59 h, although the difference was not significant. The results of present study are in agreement with the previous findings that reported lesser t 1/2 of investigated drug in HL rats ( Katnapally et al, 2009 , Khalil et al, 2017 , Khalil et al, 2016 ). The CL of Gb in NL rats was recorded as 2.53 ml/h while the CL in HL rats was noted as 1.39 ml/h.…”
Section: Resultssupporting
confidence: 94%
“…HL was induced by single intraperitoneal injection of 1 g/kg of Poloxamer-407. Control and the HL groups were dosed with the drug; HL group were treated after 36 h from the P407 injection ( Chaudhary and Brocks, 2013 , Khalil et al, 2017 , Khalil et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Restricted transmembrane transport caused by protein binding results in a reduction in metabolism and excretion and an elevation of plasma concentrations, which fits with the findings of M10 31 . However, this study did not find a relationship between albumin and PK parameters, indicating that the CL/F of posaconazole may be influenced by other plasma-binding proteins such as lipoprotein 59,60 and C-reactive protein (CRP) 54 . M2 24 found that posaconazole exposure decreased with the baseline bilirubin [?]…”
Section: Discussioncontrasting
confidence: 71%
“…The transport of pharmaceutical components is varied due to the interaction between the components [12]. Thus, it is necessary to further study and quantitatively express the interaction and change process of chemical composition in vivo [13,14]. The plasma concentration method can provide scientific and objective pharmacokinetic parameters reveal the rationality of compatibility, which provides scientific basis for the optimization of prescription compatibility and clinical application [15,16].…”
Section: Introductionmentioning
confidence: 99%